KOMUNIKASI VERBAL DALAM PENGEMBANGAN PEMBELAJARAN BAHASA ARAB BERBASIS MEDIA BITHAQAH AL-JAIBIYAH - Achmad Muhlis (IAIN MADURA, 2016)
Verbal communication in the development of learning of the Arabic Language based media bithaqah jaibiyah, is a must for every teacher of Arabic language in any development of tazwidul mufrodat which in the end going to support, encourage and motivate students, both in speaking skills (maharah al-kalam), Listening (maharah istima’), reading (maharah qiro’ah), and also writing (maharah kitabah). Verbal communication in teaching learning of arabic by using media bithaqah al-jaibiyah, can be done and applied through two activities at once in any learning, namely: pre workout communication and communication exercises. In pre workout communication, there are some techniques which is very possible, such as : memorization of the dialog (al-hifdz ‘ala al-hiwar), dialog through images (al-hiwar bi al-suwar), guding dialog (al-hiwar al-muwajjah), a dramatization of the action (al-tamtsil al-suluki), technique on practice patterns (tathbiq al-namadzij). While the activities that can be done in the exercise of communication are, among others: group of conversations (al-hiwar al-jama’i), role play (al-tamtsil), social utterance practice (tathbiq al-ta’birat al-ijtima’iyah), field practice (al-mumarasah fi al-mujtama’), solving problem (hill al-musykilat). The Communication on Arabic learning through media bithaqah al-jaibiyah, going to success if we could develop dan improve students motivation, interests and talents of students itself in the use and utilize the media bithaqah jaibiyah, that the same use proportionally and professionally by the teacher in the field of study of the Arabic language so that the out put that is produced in accordance with the expectations and targets set out in the standards of competence of graduates of a madrasah or school.